2023
DOI: 10.1097/yct.0000000000000914
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Tolerability of Continuation and Maintenance Electroconvulsive Therapy for Depression

Abstract: Electroconvulsive therapy (ECT) is a highly effective treatment for severe and treatment-resistant depression, but relapse rates remain high despite maintenance pharmacotherapy. Continuation or maintenance ECT (C/M-ECT) offers the potential to prevent relapses in the most unwell patients, but there remains disagreement among guidelines regarding its efficacy and tolerability. This review aims to summarize and assess the current evidence for the efficacy and tolerability of continuation and maintenance ECT for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
(133 reference statements)
0
2
0
Order By: Relevance
“… 10 , 26 , 27 In regards to the cognitive adverse effect, data from previous studies indicated that the continuation and maintenance ECT do not appear to have a harmful effect for global cognitive function. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 26 , 27 In regards to the cognitive adverse effect, data from previous studies indicated that the continuation and maintenance ECT do not appear to have a harmful effect for global cognitive function. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…10,26,27 In regards to the cognitive adverse effect, data from previous studies indicated that the continuation and maintenance ECT do not appear to have a harmful effect for global cognitive function. 28,29 Strengths of this study was the inclusion of patients with various psychiatric diagnoses. The study also used objective measures of hospitalization and admission days before and after continuation-maintenance ECT, which adds to the validity of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it well known that ECT is effective for depression (Rowland et al, 2023) but it's efficacy on depressive symptoms was not evaluated in patients with CRS in the Chinese studies (Wang et al, 2018), whereas in the US study depressive symptoms were evaluated by the Hamilton Depression Rating Scale (Hamilton, 1960), which is not as specific as the Calgary Depression Rating Scale, designed for the evalution of depressive symptoms in schizophrenia (Bressan et al, 1998).…”
Section: -Introductionmentioning
confidence: 99%